In vitro study of marginal, internal and proximal adaptation of implant-supported single-crown CAD/CAM restorations - Kamila Aguiar Figueiredo Alves; Janaina Emanuela Damasceno; Viviane Maia Barreto de Oliveira; Luiz Gustavo Cavalcanti Bastos; Andrea Nóbrega Cavalcanti (Universidade Estadual de Campinas, 2020)
Aim: This study evaluated the precision of a CAD/CAM system by measuring marginal, internal and proximal fits in implantsupported single-crown restorations. Methods: Ten models of the upper arch were made in which implants replaced the upper left premolars. For fabrication of the zirconia infrastructures, titanium bases (TiBase) were coded and scanned using a scan body. A second digital impression was made for the fabrication of prostheses. Silicone impression material was used to determine the internal clearance between the TiBase and infrastructure and between the infrastructure and crown, whose thickness was measured at three points [P1 (cervical), P2 (middle) and P3 (occlusal)] with a stereoscopic microscope at 70x and 100x magnification. One-way ANOVA for repeated measures and the Student t-test were used for the analysis of internal and marginal adaptation. Proximal contacts were analyzed qualitatively. Results: There was no significant difference between the teeth evaluated (Student's t-test; p>0.05) or between the corresponding points evaluated in either tooth (one-way ANOVA; p>0.05). Analysis of the internal clearance between the infrastructure and crown demonstrated that all points were significantly different compared to the reference standardized at 100 μm (Student's t-test p<0.0001). There was no significant difference between P1 and P2, with the thickness at these two points being lower than that obtained at P3 (one-way ANOVA, p<0.05). The proximal contacts did not coincide with the quality defined by the device. Conclusion: The system tested was unable to produce implantsupported single-crown ceramic restorations with marginal, internal and proximal fits matching the digital workflow, with the inferior fits requiring adjustment prior to cementation.